Wheat morpho‐physiological traits and radiation use efficiency under interactive effects of warming and tillage management. (20th November 2020) - Li, Yibo; Hou, Ruixing; Tao, Fulu
Abstract: Understanding the interactive effects of different warming levels and tillage managements on crop morphological and physiological traits and radiation use efficiency (RUE) is essential for breeding climate‐resilient cultivars. Here, we conducted temperature free‐air controlled enhancement (T‐FACE) experiments on winter wheat during two growth seasons in the North China Plain. The experiments consisted of three warming treatments and two tillage treatments (CT: conventional tillage and NT: no‐tillage). In the normal season, warming had significant positive effects on major morphological and physiological traits and increased significantly RUE of yield (RUEY ) and biomass (RUEDM ) by 13.3 and 11.3%, 19.3 and 12.4%, 42.3 and 43.7%, respectively, under the treatments of CTT1, CTT2 and NTT1 relative to the control (CTN, NTN). By contrast, in the warmer season, warming had negative effects on leaf width, light extinction coefficient, light‐saturated net photosynthetic rate, aboveground, stems and spike biomass and RUE from anthesis to maturity, and consequently grain yield under conventional tillage, but positive effects under no‐tillage. Our findings bring new insights into the mechanisms on the interactive effects of warming and tillage treatments on wheat growth and productivity; provide valuable information on crop ideotypic traits for breeding climate‐resilient crop cultivars. Abstract : Understanding the interactive effects of different warming levels and tillage managements on crop morphological and physiological traits and radiation use efficiency (RUE) is essential for breeding climate‐resilient cultivars, which, however, have rarely been investigated. Here, we conducted temperature free‐air controlled enhancement (T‐FACE) experiments on winter wheat during two growth seasons (2018/19, 2019/20) in the North China Plain. The experiments consisted of three warming treatments (CK: no warming, T1: warming 1.3°C and T2: warming 2.3°C above ambient temperature) and two tillage treatments (CT: conventional tillage and NT: no‐tillage). We investigated the interactive effects of different warming levels and tillage managements on winter wheat morphological and physiological traits and radiation use efficiency. The results showed that the interactive effects of warming and tillage treatments had major impacts on wheat morphological and physiological traits, and subsequently on canopy light interception, photosynthesis, biomass and RUE. In the normal season (2018/19), warming had significant positive effects on major morphological and physiological traits and increased significantly RUE of yield (RUEY ) and biomass (RUEDM ) by 13.3 and 11.3%, 19.3 and 12.4%, 42.3 and 43.7%, respectively, under the treatments of CTT1, CTT2 and NTT1 relative to the control (CTN, NTN). By contrast, in the warmer season (2019/20), warming had negative effects on leaf width, light extinction coefficient, light‐saturated net photosynthetic rate, aboveground, stems and spike biomass, and RUE from anthesis to maturity and consequently grain yield under conventional tillage, but positive effects under no‐tillage. Our findings bring new insights into the mechanisms on the interactive effects of warming and tillage treatments on wheat growth and productivity; provide valuable information on crop ideotypic traits for breeding climate‐resilient crop cultivars.